Economic downturns and mental wellbeing - Daniel Avdic; Sonja C. de New; Daniel A. Kamhöfer (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We study the impact of the business cycle on mental wellbeing by linking rich German survey data to over a decade of detailed gross domestic product information. Endogeneity concerns are tackled using a shift-share instrumental variables approach in which exposure to macroeconomic fluctuations is estimated from regional variations in historical industry sector composition. Estimation results reveal strong negative effects of economic downturns on both life satisfaction and a multidimensional measure of mental health. We provide evidence that these effects are mediated by fear of job loss and income reductions, while actual unemployment effects are negligible. A case study of the impact of the global financial crisis reveals that adverse effects on mental wellbeing are persistent and remained even after the economy recovered.
Keywords: C36; E32; I15; 330; business cycle; mental health; life satisfaction; global financial crisis; shift-share instrument